Processo de compostagem com diferentes porcentagens de resíduos sólidos agroindustriais - Silva, Lucimar Novaes da (2007)
This assignment was developed at Coopavel Cooperativa Agroindustrial plant situated in the city of Cascavel, Parana, Brazil, positioned at 24º 58 04,7 S and 53º22 51,1 W with an altitude of 2,378.61 feet (725 metrs). The region climate is classified as Cfa according to KÖPPEN`s categorization with moderate temperature, well distributed rain fall, hot summers, and an annual average temperature of 21ºC. This work aimed to evaluate percentages of agro industrial solid residues through composting process, identifying the mixture that allow for better performance of the process, as well as the one that would give origin to the final product with better quality. Treatments were as follows: T1 (167 Kg of ruminal residue + 167 Kg of incubatory residues + 167Kg of ceral residues + 166 Kg of lake residue + 166Kg of floater + 167 Kg of ash); T2 (150 Kg of ruminal residue + 150 Kg of incubatory residue + 130 Kg of cereal residues + 120 Kg of lake residue + 250 Kg + 150 Kg of floater residues + 300 Kg of ash); T3 (250 Kg of ruminal residue + 250 Kg of incubatory residue + 100 Kg of cereal residue + 50 Kg of lake residue + 50 Kg od floater residue + 300 Kg of ash) ; T4 (267 Kg of ruminal residue + 300 Kg of incubatory residue + 266 Kg of cereal residue + 167 Kg of lake residue); T5 (300 Kg of ruminal residue + 300 Kg of incubatory residue + 200 Kg of cereal residue + 100 Kg of lake residue + 100 Kg of floater residue), each pile weighed 1000 Kg, repeated twice, with random block experimental delimitation. Chemical characterization of the many residues was executed as well as chemical analysis of cured compound. Parameters evaluated during the experimental period where daily ambient and each vivarium temperature, Ph, humidity and weekly volume reduction of each vivarium, initial and final weight of each vivarium. Average temperature demonstrated that T4 and T5 treatments maintained the highest temperature until the 14th week compared to the other treatments. Largest volume reduction was noted in T1 and T4 treatments with a reduction of 48.17% and 45.20% respectively. The largest weight reductions occurred in T4 and T5 treatments with a 60.85% and 58.05% reduction respectively. In the treatments where ash was employed in their composition were the ones that a better attribute as far as the final composting quality is concerned when analyzing micronutrients.